Development Of Marketing Strategy Of PT. Sas Aero Sishan With SWOT Analysis Approach In Order To Improve Company Performance - Danil Pratama Putra; Warkianto Widjaja (UNIVED Press, 2026)
This abstract discusses the analysis of PT Sas Aero Sishan's marketing strategy using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. SWOT analysis is conducted to identify internal factors in the form of strengths and weaknesses, as well as external factors in the form of opportunities and threats that affect the company's marketing. Based on the results of the analysis, PT Sas Aero Sishan has six strengths, two weaknesses, five opportunities, and three threats, with an IFAS matrix value of 2.99 and EFAS of 2.6. The resulting strategy focuses on maximizing promotions and continuous bookings to face competition and the impact of the COVID-19 Pandemic.